2017
DOI: 10.3390/app7010088
|View full text |Cite
|
Sign up to set email alerts
|

Strong Aftershock Study Based on Coulomb Stress Triggering—A Case Study on the 2016 Ecuador Mw 7.8 Earthquake

Abstract: Abstract:The 2016 Ecuador M 7.8 earthquake ruptured the subduction zone boundary between the Nazca plate and the South America plate. This M 7.8 earthquake may have promoted failure in the surrounding crust, where six M ≥ 6 aftershocks occurred following this mainshock. These crustal ruptures were triggered by the high coulomb stress changes produced by the M 7.8 mainshock. Here, we investigate whether the six M ≥ 6 aftershocks are consistent with the positive coulomb stress region due to the mainshock. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The previous study showed that the µ' is typically found to be around 0.4 for subduction zones [10]. Figure 6 shows Coulomb stress change distribution of Halmahera earthquake on June 7th, 2016 with depth of 47 km and Mw: 6.3.…”
Section: Coulomb Stress Change Solutionmentioning
confidence: 89%
“…The previous study showed that the µ' is typically found to be around 0.4 for subduction zones [10]. Figure 6 shows Coulomb stress change distribution of Halmahera earthquake on June 7th, 2016 with depth of 47 km and Mw: 6.3.…”
Section: Coulomb Stress Change Solutionmentioning
confidence: 89%
“…In addition, various researchers have assimilated the fault plane solutions in computing the Coulomb stress variation (Hardebeck et al, 1998;Meier et al, 2014;Asayesh et al, 2020). Furthermore, using the Coulomb stress analysis, several researchers have inferred that the fault planes may undergo induced stress along the nodal planes ( Wu et al, 2017;Asayesh et al, 2020). The present study is focused on two consequent significant earthquakes (M4.6 of July 2020 and M4.2 of December 2020) that had occurred in the northern part of the Alwar district and to the southwest of the Delhi NCR, within a very short span of time of about 5 months.…”
Section: Coulomb Stress Change Analysismentioning
confidence: 99%
“…According to Utsu (1970) , for a main earthquake with a magnitude of 7, the time difference is generally in the range 0.01-100 days and the range gets larger with the magnitude of main shock. To give examples, for 1999 Marmara Earthquake, the largest aftershock is 27 days later than the main shock ( Örgülü and Aktar, 2001 ), and this time is 17 and 32 days for 2015 Nepal ( Wikipedia, 2018 ) and 2016 Ecuador ( Wu et al, 2017 ) earthquakes, respectively.…”
Section: Introductionmentioning
confidence: 99%